Symposium 2: The Social Life of Data Clusters: The Potential of Sociomaterial Analysis in the Critical Study of Educational Technology - Perrotta, Carlo (Proceedings of the International Conference on Networked Learning, 2016)
This paper draws on Actor-Network Theory to argue that methods used for the classification and measurement of online education are not neutral and objective but are involved in the creation of the educational realities they claim to measure. The paper examines Cluster Analysis (CA) as a ‘performative device’ that, to a significant extent, creates the educational entities it claims to objectively and neutrally represent through the emerging body of knowledge of Learning Analytics (LA). In the conclusion, the paper suggests that those concerned with social justice in educational technology need not limit themselves to denouncing structural inequalities and ideological conflicts. At the opposite end of the ‘critical spectrum’ there is the opportunity to analyse in a more descriptive fashion how hegemonic discourses in education are legitimated through techniques and devices.